Overexpression of a pseudo-etiolated-in-light-like protein in Taraxacum koksaghyz leads to a pale green phenotype and enables transcriptome-based network analysis of photomorphogenesis and isoprenoid biosynthesis - Wolters, Silva Melissa; Benninghaus, Vincent Alexander; Roelfs, Kai-Uwe; van Deenen, Nicole; Twyman, Richard M.; Prüfer, Dirk; Schulze Gronover, Christian (Frontiers in Plant Science, 2023)
Plant growth and greening in response to light require the synthesis of photosynthetic pigments such as chlorophylls and carotenoids, which are derived from isoprenoid precursors. In Arabidopsis, the pseudo-etiolated-in-light phenotype is caused by the overexpression of repressor of photosynthetic genes 2 (RPGE2), which regulates chlorophyll synthesis and photosynthetic genes. We investigated a homologous protein in the Russian dandelion (Taraxacum koksaghyz) to determine its influence on the rich isoprenoid network in this species. Homology-based screening revealed a gene designated pseudo-etiolated-in-light-like (TkPEL-like), and in silico analysis identified a light-responsive G-box element in its promoter. TkPEL-like overexpression in dandelion plants and other systems reduced the levels of chlorophylls and carotenoids, but this was ameliorated by the mutation of one or both conserved cysteine residues. Comparative transcriptomics in dandelions overexpressing TkPEL-like showed that genes responsible for the synthesis of isoprenoid precursors and chlorophyll were downregulated, probably explaining the observed pale green leaf phenotype. In contrast, genes responsible for carotenoid synthesis were upregulated, possibly in response to feedback signaling. The evaluation of additional differentially expressed genes revealed interactions between pathways. We propose that TkPEL-like negatively regulates chlorophyll-and photosynthesis-related genes in a light-dependent manner, which appears to be conserved across species. Our data will inform future studies addressing the regulation of leaf isoprenoid biosynthesis and photomorphogenesis and could be used in future breeding strategies to optimize selected plant isoprenoid profiles and generate suitable plant-based production platforms.